Detection of new single nucleotide polymorphisms in plasma cells carcinoma (myeloma) by polymerase chain reaction–single strand conformation polymorphism and sequencing technical methods - Sarah K. Obayes; Sabah H. Enayah; Shaimaa A. Al-Oubaidy; Rana A. Ghaleb (Medical Journal of Babylon)
Abstract Background: MicroRNA (miRNA) is a short, single-stranded, non-coding sequence of RNA that does not translate into proteins. Because of their ability to control gene expression, recent studies have shown that these short, non-coding sequences play an important role in cancer. So that, detection the polymorphisms or variants in miRNA genes may help to identify their correlation to cancer susceptibility. Objectives: Study the polymorphisms in miRNA genes or variants miRNA genes and their correlation with myeloma disease. Materials and Methods: Twenty samples were collected from people who visited Marjan Hospital in Province of Babylon, Iraq, from February to July 2022. In addition, 20 samples from healthy people were collected as control. Genotyping of miRNA was accomplished using the polymorphism techniques of polymerase chain reaction and single strand conformation polymorphism (SSCP). DNA sequencing was also applied to categorize all the ranges of SSCP models detected using only gel imaging. Results: The genotypes obtained in this experiment verified that several single nucleotide polymorphisms were obtained between 5-band and 6-band miRNA National center for biotechnology information Primer3 plus reference. Conclusion: The results explain that the miRNA gene polymorphisms may have correlation with the susceptibility to myeloma disease.